PENYELESAIAN MASALAH BAYI TABUNG MELALUI ISTINBATH HUKUM DALAM KITAB AL-BURHAN FI USHUL FIQH KARYA IMAM HARAMAIN AL-JUWAINI - Abd. La’lang- (STIT Muhammadiyah Paciran Lamongan, 2025)
This study examines the Islamic ruling on in vitro fertilization (IVF) based on the Al-Burhan fi Ushul al-Fiqh by Imam Haramain Al-Juwaini. The methodology employed includes Qiyas (Analogy), Istihsan (Legal Preference), Sadd al-Dzari’ah (Blocking Harmful Means), and Maslahah (Public Interest in Islamic Law). The findings indicate that IVF is permissible within the boundaries of Islamic law, provided that it does not involve sperm or egg donation, surrogate motherhood, and that lineage remains legally clear. Qiyas links IVF to lineage laws, stipulating that fertilization should occur exclusively between a legally married couple. Istihsan allows IVF in cases of necessity to safeguard couples unable to conceive naturally. Sadd al-Dzari’ah emphasizes the prohibition of any practice that could lead to lineage confusion. Meanwhile, Maslahah justifies IVF when it aligns with maqashid syariah and serves the welfare of those in need. The study underscores the importance of balancing medical advancements with Islamic legal principles, calling for regulations that adhere to Islamic ethics and maqashid syariah to preserve lineage integrity and social justice.